Transformasi Etika Profesi Pendidik dalam Mewujudkan Pendidikan Islam Berkarakter - Muhammad Ismed Suhanda; Riski Romadhan; Sahrul Romadhon Al Amin; Syafaatul Habib (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The ethics of the teaching profession are the main pillars in the implementation of Islamic education with character. The transformation of professional ethics does not only concern the scientific and professional aspects, but also the spiritual, moral, and social dimensions. This study aims to examine the role of the transformation of the ethics of the teaching profession in shaping the character of students based on Islamic values. The research method used is a literature study with a descriptive qualitative approach. The results of the study indicate that the transformation of the ethics of the teaching profession involves increasing integrity, moral responsibility, sincerity in teaching, and exemplary behavior that is sourced from Islamic teachings. The implementation of this ethics consistently can create Islamic education that is not only intellectually intelligent, but also has a strong and religious character.